EFFECT OF EPLERENONE ON SERUM LEVEL OF SOLUBLE GROWTH-STIMULATING RECEPTOR EXPRESSED BY GENE 2 IN PATIENTS WITH ARTERIAL HYPERTENSION - Bilovol, O.M.; Knyazkova, I.I.; Golovacheva, V.O.; Kuzminova, N.V.; Barbashova, V.O.; Molodan, D.V.; Bogun, M.V. (World of Medicine and Biology, 2022)
The purpose of the work was to study the dynamics of diastolic function parameters, the content of the soluble growth-stimulating receptor expressed by gene 2 (sST2) and the N-terminal fragment of the brain natriuretic propeptide (NT-proBNP) in the blood of patients with hypertension, when eplerenone is added to antihypertensive therapy. In patients with stage 2 arterial hypertension, addition of eplerenone to antihypertensive therapy contributes to a more pronounced decrease of blood pressure measured by patients during self-monitoring; during daily monitoring compared to antihypertensive therapy. The inclusion of the selective aldosterone mineralocorticoid receptor antagonist eplerenone in the complex therapy of patients with stage 2 arterial hypertension has a pronounced positive effect on the structural and geometric indicators of the myocardium, parameters of the diastolic function of the left ventricle, as well as the content of sST2 and NT-proBNP in the blood serum, along with good tolerability.